Engineering secure software and systems third international symposium, ESSoS 2011, Madrid, Spain, February 9-10, 2011. proceedings - Erlingsson, Ulfar; Wieringa, Roel; Zannone, Nicola (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Third International Symposium on Engineering Secure Software and Systems, ESSoS 2011, held in Madrid, Italy, in February 2011. The 18 revised full papers presented together with 3 idea papers were carefully reviewed and selected from 63 submissions. The papers are organized in topical sections on model-based security, tools and mechanisms, Web security, security requirements engineering, and authorization.